2020
DOI: 10.21608/bnni.2020.108368
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Early Life Giardiasis on Growth, Nutritional Status, and Serum Trace Elements in Children

Abstract: iardia lamblia is considered the most common intestinal parasite in humans worldwide. Giardiasis is a major health problem with a great morbid effect on children's physical and cognitive development. The aim of this work was to evaluate the effect of giardiasis on children's growth, assess the serum levels of zinc, copper, and iron, also to study the relation between giardia infections and breastfeeding. Methods: this was a crosssectional study carried out on 200 children (1-3 years). They were recruited from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…As evidenced by a significant decrease in the Z -score for weight, height, and head circumference in the Giardia -infected children, it has been observed that a lack of trace elements has an effect on children's growth [ 54 ]. Another study found that serum zinc levels significantly influenced anthropometric measurements, especially body weight and BMI [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…As evidenced by a significant decrease in the Z -score for weight, height, and head circumference in the Giardia -infected children, it has been observed that a lack of trace elements has an effect on children's growth [ 54 ]. Another study found that serum zinc levels significantly influenced anthropometric measurements, especially body weight and BMI [ 55 ].…”
Section: Discussionmentioning
confidence: 99%